Enterprise Risk Management, Value Chain, And Life Cycle Cost: How The Three Concepts Are Adopted To Increase Competitiveness. - Antonius ALIJOYO (International Journal of Environmental, Sustainability, and Social Science, 2022)
Enterprise Risk Management (ERM), Value Chain VC), and Life Cycle Cost (LCC) are three crucial concepts in running an effective company. Hence, no specific study has been done to identify how those concepts were implemented in companies in Indonesia. Thus, the study objective was to identify types of ERM used by the companies, how they connect the ERM to VC and LCC, and how effective the combination of the three concepts to enhance companies’ competitiveness was. The study data were collected through focus groups discussion and interviews. This study involved some scholars and selected professionals who were the senior management of corporations listed in IDX. The FGD and interview results were analyzed qualitatively through an interactive data analysis model. The study found that most companies applied the ISO 31000 as their ERM. The respondents agreed that ERM was used as the basis for setting and managing prices that support the implementation of VC and LCC. Besides, they also believed that the integration of the concepts was effective in increasing competitiveness. Since this study was conducted qualitatively, the result of the study needs to be supported by a further study using a quantitative approach to strengthen the result of the study so that it can be generalized to a bigger population.